Diversity and Abundance Seed-Eating Birds in Tanjungsari Rice Fields Area, Tulungagung - Kartikasari, Desi; Abidin, Ali; Agustina, Citra Sari; Nurdianyoto, Indra (LenteraBio : Berkala Ilmiah Biologi, 2024)
The presence of seed-eating birds is often troubling and a threat to farmers, because these birds consume rice grains that are ready for harvest or are still young and cause rice production to decline. This study aims to analyse the diversity and abundance of seed-eating birds in Tanjungsari rice fields. The research was conducted in May-June 2023 at three observation stations in the rice fields of Tanjungsari Village. The techniques used were observation and field surveys using the free range method according to the path in the rice fields that have been determined (purposive sampling). Based on the results of the study obtained 6 species of seed-eating birds from 3 families, namely Lonchura leucogastroides, Lonchura maja, Lonchura punctulata, Passer montanus, Streptopelia chinensis and Pycnonotus aurigaster. The diversity index of seed-eating birds in the Tanjungsari rice field area is included in the medium category with an average value of 1.7, indicating that the Tanjungsari rice field area has a fairly good vegetation and community composition for the survival of seed-eating bird species. The largest percentage of total relative abundance of seed-eating birds is the scale-breasted bondol (Lonchura punctulata) at 26.38% and the Javan bondol (Lonchura leucogastroides) at 22.92%. The presence of this type of bondol bird can be a pest in agricultural land, because it attacks rice plants in clusters during the grain maturation phase until ready to harvest, causing losses to farmers.